Construcciones focalizadoras y oralidad - Ruiz Velasco D., Liliana (2018)
This paper addresses three Spanish focus constructions: clefts, the Det+N+ ser construction (e.g. la verdad es que...), and the lo+adj+ser construction (e.g. lo bueno es que...). Since their status in the oral-written dimension is still ambiguous and it has even been proposed some closeness with the written language, the research focused on their frequency in an oral corpus of Mexican Spanish, as well as their discourse functions. The data collected shows that these constructions are more frequent in the telenovela, while among non-fictional genres they are linked to those situated within the communicative immediacy space (v. Koch y Oesterreicher 1985). Their functions are grouped in two dimensions: micro- and macrotextual; the latter being the prevailing one since by using these constructions the speaker organizes and marks topical lines in discourse.